Nonlinear observer-based Lyapunov boundary control of distributed heat transfer mechanisms for membrane distillation plant. (November 2016) - Eleiwi, Fadi; Laleg-Kirati, Taous Meriem
Abstract : Highlights: We propose an observer-based nonlinear Lyaponov control for membrane distillation. The system is modeled by a two dimensional advection diffusion equation The controller considers the inlet, feed and permeate, temperatures as input. The controller maintains the water production around a desired value. A nonlinear observer has been developed to estimate the temperatures. Abstract: This paper presents a nonlinear observer-based Lyapunov control for a membrane distillation (MD) process. The control considers the inlet temperatures of the feed and the permeate solutions as inputs, transforming it to boundary control process, and seeks to maintain the temperature difference along the membrane boundaries around a sufficient level to promote water production. MD process is modeled with advection diffusion equation model in two dimensions, where the diffusion and convection heat transfer mechanisms are best described. Model analysis, effective order reduction and parameters physical interpretation, are provided. Moreover, a nonlinear observer has been designed to provide the control with estimates of the temperature evolution at each time instant. In addition, physical constraints are imposed on the control to have an acceptable range of feasible inputs, and consequently, better energy consumption. Numerical simulations for the complete process with real membrane parameter values are provided, in addition to detailed explanations for the role of the controller and the observer.